1995
DOI: 10.1029/94jc02765
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter and phytoplankton and bacterial biomass distributions in the Northeast Water Polynya during summer 1992

Abstract: The patterns of particulate matter distribution (chlorophyll, phytoplankton pigmentation, biogenic silica, particulate carbon, and nitrogen, bacterial and phytoplankton abundance, and optical particle concentration) in the Northeast Water Polynya off the northern coast of Greenland are described, and their relationships to environmental conditions (hydrography, nutrients, and ice cover) are analyzed. Particulate matter concentrations were substantial in the euphotic zone, with the largest fraction consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…They attributed this to grazing of herbivorous copepods, which is about 3 times higher in the south (Ashjian et al 1995). Ambrose & Renaud (1995) found no relationship between water-column and benthic pigment concentration (the most important predictor of infaunal density and polychaete biomass) in the Southern Trough, although phytoplankton standing crops were similar to those in the Northern Trough (Smith et al 1995) In their opinion this might indlcate that water column and benthos were decoupled in the south, possibly due to the abundance of grazing phytoplankton. Pomeroy (1974) and Jumars et al (1989) suggested that grazers are needed to stimulate bacterial activity (by providing substrate of high quality); the grazers should enhance the role and importance of the microbial loop in processing carbon.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They attributed this to grazing of herbivorous copepods, which is about 3 times higher in the south (Ashjian et al 1995). Ambrose & Renaud (1995) found no relationship between water-column and benthic pigment concentration (the most important predictor of infaunal density and polychaete biomass) in the Southern Trough, although phytoplankton standing crops were similar to those in the Northern Trough (Smith et al 1995) In their opinion this might indlcate that water column and benthos were decoupled in the south, possibly due to the abundance of grazing phytoplankton. Pomeroy (1974) and Jumars et al (1989) suggested that grazers are needed to stimulate bacterial activity (by providing substrate of high quality); the grazers should enhance the role and importance of the microbial loop in processing carbon.…”
Section: Discussionmentioning
confidence: 93%
“…The incongruence in our findings concerning the lower abundance of peracarids in the south, where the chlorophyll incorporation and biological activity (ATP measurements) are not strikingly lower, might indicate a greater abundance of smaller meiobenthic organisms in the south, which could lead to a most rapid incorporation of organic matter into the sediment by bioturbation processes. On the other hand, Ambrose & Renard (1995) implicate a possible grazing effect of copepods for the lower densities of polychaetes in the southern trough (Ashjian et al 1995, Smith et al 1995. Grazing would also affect the availability of food for peracarids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) ranges between -74 and -44 mmol C m Bacterial production was computed as the product of bacterial biomass and growth rates. Data from Smith et al (1995), Yager (1996) and Yager & Deming (1999) Th disequilibrium (E TH ), and computed bacterial respiration (BR, Eq. 14) and export (E T = P T -R, Eq.…”
Section: Comparing the Model With Independent Datamentioning
confidence: 99%
“…In addition, because there are no published PB data for the Peruvian upwelling system, we used instead those for the Chilean upwelling (McManus & Peterson 1988, Ducklow & Carlson 1992. BP in the NEW was computed from published bacterial growth rates and bacterial biomass (Smith et al 1995, Yager 1996, Yager & Deming 1999. Values of E TH are from Buesseler (1998), Charrette et al (1999) and Buesseler et al (2001).…”
Section: Comparing the Model With Independent Datamentioning
confidence: 99%